A Breathing Atom‐Transfer Radical Polymerization: Fully Oxygen‐Tolerant Polymerization Inspired by Aerobic Respiration of Cells. (2nd January 2018) - Enciso, Alan E.; Fu, Liye; Russell, Alan J.; Matyjaszewski, Krzysztof
Abstract: The first well‐controlled aqueous atom‐transfer radical polymerization (ATRP) conducted in the open air is reported. This air‐tolerant ATRP was enabled by the continuous conversion of oxygen to carbon dioxide catalyzed by glucose oxidase (GOx), in the presence of glucose and sodium pyruvate as sequential sacrificial substrates. Controlled polymerization using initiators for continuous activator regeneration (ICAR) ATRP of oligo(ethylene oxide) methyl ether methacrylate (OEOMA, Mn =500) yielded polymers with low dispersity (1.09≤ Đ ≤1.29) and molecular weights (MWs) close to theoretical values in the presence of pyruvate. Without added pyruvates, lower MWs were observed due to generation of new chains by H2 O2 formed by reaction of O2 with GOx. Successful chain extension of POEOMA500 macroinitiator with OEOMA300 (Đ≤1.3) and Bovine Serum Albumin bioconjugates (Đ≤1.22) confirmed a well‐controlled polymerization. The reactions in the open air in larger scale (25 mL) were also successful.